Conditioning of graphene surface by CO2cluster jet - Choi,H; Kim,JA; Cho,Y; Hwang,T; Lee,J; Kim,T (RSC Advances, 2014)
© the Partner Organisations 2014. The reduction of resistance and surface roughness obtained by CO2cluster jet were up to 81% and 42.3% compared with pristine graphene. The shifts in Raman spectra also implied chemical doping and "mono-layerization". Thus, CO2cluster jet has the potential for planarization, cleaning and flattening of the graphene. This journal is